Izzy Lyon : the unspun truth [videorecording (DVD)] - Torgoley, Mehran; Barron, Llana; Lanigan, Dan; Klimczak, Andy; Lamarr, Phil, 1967-; Baum, Bruce, 1952-; Koechner, David, 1962- (Octane Multimedia, 2023)
Izzy Lyon: The Unspun Truth dives into the life, and loves of the greatest sign spinner of all time. From his meteoric rise to his tragic fall, this comedy paints a hilarious portrait of the man once referred to as "the Picasso of Sign Spinning."